Discovery of a Selective S1P(1) Receptor Agonist Efficacious at Low Oral Dose and Devoid of Effects on Heart Rate - Demont, Emmanuel H. (American Chemical Society, 2011)
[Image: see text] Gilenya (fingolimod, FTY720) was recently approved by the U.S. FDA for the treatment of patients with remitting relapsing multiple sclerosis (RRMS). It is a potent agonist of four of the five sphingosine 1-phosphate (S1P) G-protein-coupled receptors (S1P(1) and S1P(3−5)). It has been postulated that fingolimod's efficacy is due to S1P(1) agonism, while its cardiovascular side effects (transient bradycardia and hypertension) are due to S1P(3) agonism. We have discovered a series of selective S1P(1) agonists, which includes 3-[6-(5-{3-cyano-4-[(1-methylethyl)oxy]phenyl}-1,2,4-oxadiazol-3-yl)-5-methyl-3,4-dihydro-2(1H)-isoquinolinyl]propanoate, 20, a potent, S1P(3)-sparing, orally active S1P(1) agonist. Compound 20 is as efficacious as fingolimod in a collagen-induced arthritis model and shows excellent pharmacokinetic properties preclinically. Importantly, the selectivity of 20 against S1P(3) is responsible for an absence of cardiovascular signal in telemetered rats, even at high dose levels.